RETRACTED ARTICLE: Model Development for Village Health Volunteers Performance in Na Nang Subdistrict, Phonphisai District, Nongkhai Province - Khamhongsa, Vutpiwat (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
The objectives of this research were to: 1) assess the current conditions and needs regarding the development of a performance enhancement model for Village Health Volunteers (VHVs), 2) create and develop a performance enhancement model for VHVs, and 3) evaluate the outcomes of implementing this model in Na Nang Subdistrict, Phonphisai District, Nongkhai Province. A research and development methodology was applied. The study population included 76 VHVs in Na Nang Subdistrict, divided equally into an experimental group (38 participants) and a control group (38 participants). The experimental group participated in activities based on the performance enhancement model. The research findings were as follows: 1) The necessary operational level was higher than the actual performance level in three aspects: knowledge ( = 4.05, SD = 0.43), skills ( = 3.88, SD = 0.59), and attitude ( = 4.06, SD = 0.94). This indicated a significant need for the development of a performance enhancement model for village health volunteers in Na Nang Subdistrict, Phonphisai District, Nongkhai Province, 2) The developed model included two activities and seven key components. Learning activities focused on fostering a volunteer mindset, role acceptance, and commitment. Supportive activities emphasized teamwork, participation, societal motivation, and operational motivation, with attention to appropriateness, utility, feasibility, and comprehensiveness, and 3) The evaluation of the model implementation showed that the median score of the experimental group post-intervention was significantly higher than the pre-intervention score. Additionally, the experimental group had a significantly higher median score compared to the control group post-intervention, with statistical significance at the 0.01 level.